Pollution characteristics and source identification of soil metal(loid)s at an abandoned arsenic-containing mine, China - Ran, Hongzhen; Guo, Zhaohui; Yi, Liwen; Xiao, Xiyuan; Zhang, Li; Hu, Zhihao; Li, Changzhou; Zhang, Yunxia (Journal of hazardous materials, 2021)
Mining activities can result in serious contamination of soil by heavy metal(loid)s. In this study, the sources and spatial distribution of metal(loid)s, and the risks to public health from these metal(loid)s at an abandoned arsenic mine site were explored. The mean concentrations of arsenic (As), cadmium (Cd), mercury (Hg), manganese (Mn), lead (Pb), antimony (Sb), strontium (Sr), and thallium (Tl) in the soil in the mining area were higher than the mean background values. The main pollutants from the mining activities were As, Hg, and Sb. Five pollutant sources were identified using an approach that combined statistical methods, a positive matrix factorization model, and historical information analysis. As, Hg, Sb, and Tl were associated with the mining resources and related activities (37.29%); Mn (15.57%) and Sr (15.96%) were mainly from crustal origin and pedogenesis, respectively; Pb, Sb, and Tl were mainly from industrial sources (17.57%), and Cd was mainly from the production and application of phosphorous fertilizer (13.60%). Using incremental spatial autocorrelation crystallized that As, Hg, and Sb were mainly contained within 500 m of their source. There were formed existing non-carcinogenic hazards and carcinogenic risks from As, and potential carcinogenic risks from Cd, in the soil for those living locally. [Display omitted] •As, Hg, Sb and Tl pollution deserve special attention in arsenic-containing mine.•Integration of GIS, PCA, ISA, PMF model and field study.•Five anthropogenic sources were identified and quantified by PMF.•The soil metal(loid)s distribution, source and diffusion range were quantified.